Pemanfaatan Getah Pelepah Salak Sebagai Gel Ultrasonografi Alternatif - Susanto, Fani; Wibowo, Kusnanto Mukti; Samudra, Alan; Yuswono, Puji; Utami, Hernastiti Sedya; Cayanan, Edgardo (Poltekkes Kemenkes Semarang, 2025)
Background: Conventional ultrasound (USG) gel was generally based on carbomer 940, which was relatively expensive, difficult to access in some areas, and not environmentally friendly due to its non-biodegradable nature. This study aims to evaluate the potential of salacca leaf sap as an alternative material for a more affordable, easily obtainable, and environmentally friendly natural ultrasound gel.Methods: A quantitative experimental study was conducted on 30 adult patients. Each subject underwent two liver ultrasound examinations using carbomer 940 gel and gel from salacca leaf sap. Image assessment was conducted by three radiology specialists using the visual grading method on the parameters of parenchyma, portal vein, nodules, and artifacts. Data were analyzed using the Wilcoxon test and Cohen's Kappa test to measure inter-rater agreement.Results: The research results indicate that there is no statistically significant difference between the ultrasound images using factory gel and salacca leaf sap gel (p > 0.05). All image parameters, such as parenchymal homogeneity, visualization of the portal vein, and minimal artifacts, appeared equivalent in both types of gel.Conclusions: Salacca leaf sap shows physical characteristics that support ultrasonic wave transmission and is capable of producing liver ultrasound images comparable to commercial gel. With local availability, low cost, and environmentally friendly properties, this material has the potential to be a viable alternative to ultrasound gel that can be further developed for clinical practice and areas with limited access.